Screening for inherited thrombophilia: indications and therapeutic implications - V De Stefano; E Rossi; K Paciaroni; G Leone (Haematologica, 2002)
BACKGROUND AND OBJECTIVES: In recent years knowledge concerning inherited and acquired causes of thrombophilia has increased greatly. The most common inherited traits (deficiency in antithrombin, protein C, or protein S, factor V Leiden, prothrombin G20210A) and mild hyperhomocysteinemia are diagnosed in at least 40% of patients with venous thromboembolism (VTE). INFORMATION SOURCES: The authors work in this field, contributing to multicenter clinical and laboratory investigations and to peer-reviewed journals with original papers. The material examined in this review includes articles published in journals covered by MedLine. STATE OF THE ART: The associated risk for VTE is different according to genotype, being higher among the carriers of natural anticoagulant deficiencies and homozygotes for factor V Leiden. The overall prevalence of thrombophilic traits in the general population being near to 10% renders the probability of carrying multiple defects not excessively rare, with a further increase in thrombotic risk of up to 20-fold. Thus, clinical penetrance is heterogeneous, producing either mild or severe venous thrombotic manifestations, which can be unprovoked or associated with circumstantial risk factors and occur in either young or advanced age. More recently, inherited thrombophilia has been focused on as an important determinant of complications of pregnancy and puerperium. As expected, inherited thrombophilia produces an increased risk of VTE, particularly during puerperium. Moreover it is well established that thrombophilic women have an increased risk of late and/or recurrent fetal loss; whether they are at higher risk of pre-eclampsia, fetal growth restriction, and abruptio placentae is debated. Overall, 40% of women with obstetric complications other than VTE carry a thrombophilic trait. Yet, as a rule VTE and obstetric complications seem to occur in different individuals, probably because of the presence of unknown factors favoring one or other of these clinical manifestations. CONCLUSIONS AND PERSPECTIVES: Inherited thrombophilia is now viewed as a multicausal model, the clinical event being the result of gene-gene and gene-environment age-dependent interactions; the associated clinical manifestations can be heterogenous as regards severity as well as type of event (VTE or obstetric complication). Therefore the criteria for screening affected individuals who have suffered from the above complications or their relatives should not be very stringent. The patient's genotype could be a main determinant of the features of primary or secondary prophylaxis used in the affected individual.